2009
DOI: 10.1086/600105
|View full text |Cite
|
Sign up to set email alerts
|

Highly Effective Oral Amphotericin B Formulation against Murine Visceral Leishmaniasis

Abstract: Visceral leishmaniasis is a deadly parasitic disease caused by obligate intramacrophage protozoans of the Leishmania genus. The World Health Organization estimates the annual death toll to be 50,000, with 500,000 new cases each year. Without treatment, visceral leishmaniasis is inevitably fatal. For the last 70 years, the first line of defense has been pentavalent antimonials; however, increased resistance has brought amphotericin B to the forefront of treatment options. Unfortunately, the difficult route of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 13 publications
3
50
0
1
Order By: Relevance
“…By applying structural clustering and secondary assays to determine potency and selectivity, 70 compounds were identified that possessed 50% effective concentrations (EC 50 s) below 1 M and that did not inhibit the growth of mammalian epithelial cancer cells at this concentration. Given the need for a new small-molecule candidate for the oral treatment of leishmaniasis and our continuing efforts in this area (42)(43)(44), we decided to study selected members from the set of 70 antileishmanial molecules reported by Sharlow et al to determine whether any were candidates for further development as antileishmanial drug candidates. Several of the molecules that we evaluated displayed activity against intracellular Leishmania in vitro, and members of one class showed efficacy in a murine VL model.…”
mentioning
confidence: 99%
“…By applying structural clustering and secondary assays to determine potency and selectivity, 70 compounds were identified that possessed 50% effective concentrations (EC 50 s) below 1 M and that did not inhibit the growth of mammalian epithelial cancer cells at this concentration. Given the need for a new small-molecule candidate for the oral treatment of leishmaniasis and our continuing efforts in this area (42)(43)(44), we decided to study selected members from the set of 70 antileishmanial molecules reported by Sharlow et al to determine whether any were candidates for further development as antileishmanial drug candidates. Several of the molecules that we evaluated displayed activity against intracellular Leishmania in vitro, and members of one class showed efficacy in a murine VL model.…”
mentioning
confidence: 99%
“…Al crear depleción e, incluso, secuestro del colesterol, se evita un número mayor de amastigotes intracelulares 62 . Con base en esto y en el conocimiento de la estructura del parásito con alto contenido de ergosterol, se propuso a AmB como segunda línea de manejo y, dentro de éstas, las formas lipídicas, teniendo en cuenta su capacidad para producir menor nefrotoxicidad 63 , y la alta tasa de respuesta que se encuentra alrededor de 97% de los casos, sin haberse reportado resistencia 64 . Dentro de las formas lipídicas se prefiere AmB liposomal, ya que muestra una mayor efectividad, un aumento en su biodisponibilidad y disminución clara de los efectos adversos 65 .…”
Section: Leishmaniasisunclassified
“…[8,9,10] Acute toxicities of Amphotericin B are commonly observed and are infusion related and consists of chills, rigor, fever, aches and pains, nausea, vomiting, anorexia, dyspepsia and thrombophlebitis at the site of infusion. [11] Long term toxicity of Amphotericin B is dose related and also depends on the duration of therapy. [9] Nephrotoxicity is the most important.…”
Section: Introductionmentioning
confidence: 99%